MENGEKSPLORASI KECERDASAN BUATAN PADA MANAJEMEN PEMASARAN DIGITAL ERA 5.0 DI DUNIA UMKM - Yeni Yeni; Mohammad Kurniawan Darmaputera; Siti Komariah Hildayanti (Transpublika Publisher, 2024)
Era 5.0 is characterized by deeper integration between technology and human life, where Artificial Intelligence (AI) plays a key role in various sectors, including digital marketing. This study aims to explore how AI in the MSME world of Palembang city is applied in digital marketing, as well as its impact on marketing management strategies and results. This research uses a qualitative approach with a case study method to analyze various applications of AI in digital marketing promotions. The research results show that AI is able to increase operational efficiency, personalize content, and deeper data analysis. Apart from this, AI also helps in advertising optimization, market trend prediction, and improving customer experience. The application of AI in digital marketing faces challenges, such as data privacy issues, implementation costs, and the need for specialized expertise. AI has great potential to revolutionize digital marketing management in MSMEs, but requires a strategic and ethical approach to overcome existing challenges.